Ethical Review and Scientific Originality in the Use of Artificial Intelligence from the Perspective of Islamic Cultural History Teachers - Lubis, Reza Noprial; Saputra, Anri; Safran, Safran; Siregar, Pamonoran (Research Departement of Darullughah Wadda'wah International Islamic University Bangil, Pasuruan, 2025)
The rapid development of Artificial Intelligence (AI) has penetrated the world of education, including madrasahs; however, its use is often not accompanied by ethical awareness and scholarly originality. This study aims to analyze the ethical dimension and originality of thought in the use of AI by madrasah students, based on the perspective of Islamic Cultural History teachers at MTs Al-Ittihadiyah Medan. Using a qualitative approach with in-depth interview techniques, classroom observation, and document study, the research found that AI is used by students to complete assignments instantly, without critical thinking or spiritual reflection. This action weakens the values of academic honesty, learning responsibility, and reduces the meaning of Islamic education as a process of internalizing values. In addition, the absence of regulations and process-based assessment instruments makes it difficult for teachers to control and evaluate the authenticity of student assignments. This study contributes to the development of an Islamic digital ethics framework and emphasizes the importance of repositioning AI as an educational aid, not a substitute for the learning process. Madrasahs need to redesign policies, curriculum, and evaluation methods to maintain scholarly integrity and cultivate ethical thinking in the technological era.